Beyond Domination and Deliberation: A Foucault-Habermas Synthesis on Power, Discourse, and Critical Communication in the Digital Public Sphere: Melampaui Dominasi dan Musyawarah: Sintesis Foucault-Habermas tentang Kekuasaan, Wacana, dan Komunikasi Kritis di Ranah Publik Digital - Rudianto Widodo; Muhammad Sirajudin Fikri (jsd: Journal of Society and Development, 2026)
This article aims to analyze the relationship between communication, power, and discourse through a critical synthesis of the thought of Michel Foucault and Jürgen Habermas within the framework of critical communication theory. This study is motivated by the strengthening of communication distortions in the digital public space, when discourse is not only a means of exchanging meanings, but also a mechanism for the production of truth, normalization, opinion formation, and legitimacy of power. This study uses a qualitative approach with a critical literature review design. The research data is sourced from the primary works of Foucault and Habermas as well as supporting academic literature on critical communication theory, digital media, algorithms, public space, and surveillance capitalism. The analysis is carried out thematically-critically through the identification of key concepts, categorization of themes, comparison of Foucault-Habermas thought, and the preparation of conceptual synthesis. The findings of the study show that discourse works as a mechanism of production of a truth regime that determines what is considered legitimate, normal, and acceptable in the public sphere. In addition, modern communication is distorted when communicative actions are replaced by strategic actions controlled by political, economic, bureaucratic, media, and algorithmic interests of digital platforms. The Foucault-Habermas synthesis shows that critical communication is a dual arena: on the one hand it can be an instrument of domination, but on the other hand it can be a space of emancipation through reflective consciousness, the production of counter-discourse, and the expansion of deliberative public space. The originality of this article lies in the offer of a Foucault-Habermas conceptual synthesis to understand the dominance, distortion, and emancipation of communication in digital public spaces, especially in the context of Indonesian society